The structure of star clusters in the outer halo of M31 - Tanvir, Nial R.; Huxor, Avon P. (Monthly notices of the Royal Astronomical Society, 2012)
Abstract. We present a structural analysis of halo star clusters in M31 based on deep Hubble Space Telescope (HST) Advanced Camera for Surveys (ACS) imaging. T